Proceedings of the Proceedings of the 1st Seminar and Workshop on Research Design, for Education, Social Science, Arts, and Hum 2019
DOI: 10.4108/eai.27-4-2019.2286858
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Interactive Learning Media Based on Augmented Reality on the Achievement of Art Learning Result

Abstract: Interactive media-based art learning using AR makes the learning process become active, creative, and meaningful. The purpose of this research are to know the influence of interactive learning media based on augmented reality on students academic achievement on art learning, and to analyze students opinion about the interactive use of media based on augmented. The research design was a quasi-experimental with pre-test post-test control group design. The study was conducted with 80 students in the elementary te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…From the results of data analysis with the t test, it was found that there was a significant difference in mathematics knowledge competence before being taught using augmented reality based learning media and mathematics knowledge competence after being taught using augmented reality based learning media. Another experiment using augmented reality media also found similar results [26]. In different subject areas, the use of augmented reality can also improve student learning outcomes in learning Hinduism in elementary schools [27].…”
Section: Discussionsupporting
confidence: 53%
“…From the results of data analysis with the t test, it was found that there was a significant difference in mathematics knowledge competence before being taught using augmented reality based learning media and mathematics knowledge competence after being taught using augmented reality based learning media. Another experiment using augmented reality media also found similar results [26]. In different subject areas, the use of augmented reality can also improve student learning outcomes in learning Hinduism in elementary schools [27].…”
Section: Discussionsupporting
confidence: 53%
“…The results indicate an increase in the motivation of students, enhancing their overall learning experience, especially for those who are academically lacking. Many studies were conducted to explore the utilization of AR in elementary schools, including the usage of AR to learn natural sciences [82], geometry [92], human anatomy [93], Bengali letters [94], fine arts [95], and science [96]. Another study was conducted in 40 schools in Indonesia to examine the effects of using AR to study science in elementary schools [97].…”
Section: Preschool and Elementary School Educationmentioning
confidence: 99%
“…Mobile applications can make it straightforward to find information and services in Ar-Rahnu, an important aspect of Islamic finance. Once the account is created, users can access various features of the Ar-Rahnu mobile application.These features may include viewing available Ar-Rahnu products, submitting applications for financing, tracking the status of applications, making repayments, and accessing educational resources on financial literacy and Islamic finance (Poerwanti et al, 2019). Furthermore, the Ar-Rahnu mobile application may also provide users with notifications and reminders for upcoming repayment dates and offer personalized financial advice based on user preferences and financial goals.…”
Section: Ar-rahnu Financing Capabilities Using Mobile Applicationmentioning
confidence: 99%